Investigating Socio-Economic and Perceptual Variables of Early-Stage Entrepreneurial Activity in Selected EU Countries - Dileo, Ivano; Losurdo, Francesco (Olsztyn Economic Journal, 2016)
This paper investigates socio-economic and perceptual factors affecting the likelihood of being a total early-stage entrepreneur in selected EU countries (Denmark, Germany, Finland, Sweden and Latvia) during 2005-2012. The data used for our empirical research comes from Global Entrepreneurship Monitor (GEM). Our findings show that the probability to become a total early-stage entrepreneur increases for males and younger individuals with a bachelor’s degree or secondary education and who are working part time or full time. Furthermore, these entrepreneurs are characterised by a lower fear of failure and higher entrepreneurial skills and perception of opportunity. Policy makers should improve the institutional framework that involves measures aimed at empowering potential entrepreneurs in finding new market opportunities. Territorial cooperation in a macro-regional perspective may be a facilitator aimed at entrepreneurial development.